THE ROLE OF PHYSICAL EXPERIMENTS IN POPULARIZATION OF EXACT SCIENCES - Ledvinka, S.; Pisala, J. (Одеські астрономічні публікації, 2007)
Physical experiments play crucial role in exact sciences.We test our theories which we try give account of the world by experiments. On the one hand, themselves are an inexorable judge which one judge our conceptions about function of the world and on the other side physical experiments can demonstrate a beauty of laws of nature. The Nicholas Copernicus Observatory and Planetarium in Brno (the Czech Republic - EU) has a longtime experience with it.